Teaching Learning Pattern of Children in the Flood Area - Nurul Hartini (Faculty Psychology Surabaya University, 2011)
How does the teaching learning pattern of children in a flood area? Utilising interview, observation and focus group discussions, a study was conducted to 30 kindergarten and elementary school teachers in a flood zone in Bojonegoro region, including Dander, Trucuk, Kalitidu, Kanor, and Baureno. Results indicate that the community, particularly children have seen floods as a regular phenomenon and thus has made peace with this experience. Children motivation for going to school and learning remain intact and high in all conditions including when the flood came. The level of children's motivation for school and learning are positive potentials that should be maintained. Cooperation between the government, schools, and community are needed in order to accelerate the normalization process, particularly in developing an optimal situation for the children to learn and go to school during a flood and right after, as well.